The Systemic Response to Topical Aldara Treatment is Mediated Through Direct TLR7 Stimulation as Imiquimod Enters the Circulation. Issue 1 (December 2017) - Nerurkar, Louis; McColl, Alison; Graham, Gerard; Cavanagh, Jonathan
Abstract Topical application of Aldara cream, containing the Toll-like receptor 7/8 agonist Imiquimod, is a widely used mouse model for investigating the pathogenesis of psoriasis. We have previously used this model to study the effects of peripheral inflammation on the brain, and reported a brain-specific response characterised by increased transcription, infiltration of immune cells and anhedonic-like behavior. Here, we perform a more robust characterisation of the systemic response to Aldara application and find a potent but transient response in the periphery, followed by a prolonged response in the brain. Mass spectrometry analysis of plasma and brain samples identified significant levels of Imiquimod in both compartments at molar concentrations likely to evoke a biological response. Indeed, the association of Imiquimod with the brain correlated with increased Iba1 and GFAP staining, indicative of microglia and astrocyte reactivity. These results highlight the potency of this model and raise the question of how useful it is for interpreting the systemic response in psoriasis-like skin inflammation. In addition, the potential impact on the brain should be considered with regards to human use and may explain why fatigue, headaches and nervousness have been reported as side effects following prolonged Aldara use.